ENVIRONMENTAL MONITORING ANALYTICAL SUBSTANCES AND ANTHROPOGENIC IMPACT ON THE ENVIRONMENT (Transport systems and technologies, 2018)
The publication revealed the problem increasing the risk of human and natural substances of human origin. In an example described experimental attempts dose limiting pollutant according to the basic requirements of the monitoring system. This issue of full and effective functioning of the monitoring system within our country. Comparison and analysis of the functioning of the system of Russian regions. The methods of analytical environmental monitoring and control of content of harmful substances in the environment, food and biological tissues that meet a variety of industrial and agricultural areas. Studied the accumulation of pollutants in the environment of individual objects, their transformations and metabolic products. Deals with measures designed for the organization monitoring system of environmental pollution and assessment of human impact on it in Ukraine.
Keywords: monitoring, ecosystem, environment, persistent organic pollutants problem, the person safety